Analisis Penggunaan M-Attendance Student dengan Pendekatan TAM dan UTAUT - Bayu Nugraha; Nurhaeni Nurhaeni; M Rizki Ikhsan (LPPM STIKI MALANG, 2022)
M-Attendance is an online attendance system that can simplify the method of recording student attendance so as to reduce errors and speed up verification. This study aims to determine the success rate of implementing the M-Attendance Student system as student attendance at Sari Mulia University (UNISM) using the TAM (Technology Acceptance Model) and UTAUT (Unified Theory of Acceptance and Use of Technology) methods. The TAM method can be used to explain the factors of user behavior towards technology acceptance, user acceptance behavior towards technology, while through UTAUT it can be understood that the user's reaction and perception of technology can affect his attitude in accepting technology use. This study uses all the variables of the two methods. Measurement of the data analyzed in this study using a questionnaire distributed to 100 respondents, namely students at Sari Mulia University.Based on the results of the analysis of the TAM method, it was found that the intention to use the actual effect on the use of the system was 77%, the intention to use was influenced by the attitude towards the use of 41.7% and the perception of the usefulness of 43%, the attitude towards the use was influenced by the perception of the usefulness of 41. 5% and the perception of the ease of use of 49.7%, the perception of the ease of use affects the perception of the usefulness of 87.9%. Meanwhile, based on the results of the analysis of the UTAUT method, it was found that the intention to use and the facilitating conditions affected user behavior by 68% and 31%, usage behavior was only influenced by business expectations by 56% and social influence by 44.6%. Expectations on performance have no effect because they only get a score of 0.13%.